Morfodinâmica e morfogênese de um carste suspenso e evolução geomorfológica de longo termo: uma aproximação com base no caso do setor oeste do Curral de Pedras I / Jequitaí - Frederico Augusto Alves Goncalves (2013)
The Karstic Region of Curral de Pedras (KRCP), is located in the Sotuheast portion of the São Franciscos Craton, near the border between the cities of Jequitaí, Lagoa dos Patos and São João da Lagoa,in the state of Minas Gerais. It calls attention of researchers since the decade of the 1970´s. The name Curral de Pedras is used by locals to refer to a specific type of karst forms developed in Neoproterozoic limestone of the Lagoa do Jacaré Formation Bambuí Group. In the investigated area, outcrops of these rocks occur in the top of topographical elevations -with tubular morphology- in heights between 520m and 720m above sea level, and also along the gently inclined slopes in direction of the principal streams. These places present several karstic landforms associated with all phases of an active karstic system, namely: (i) input, (ii) storage and (iii) output of rain water. During this investigation several analyses were carried out to try to understand the morphodynamic influences and geomorphological evolution of KRCP in a specific compartment of its karst. The methods used involved in this process were cartographical techniques applied to geology and geomorphology at a scale of 1:45.000. The western sector of the Curral de Pedras I was mapped at scale of 1:100 with the main objective to point out the morphological proves of preterit hydrodynamics. Integrating these results with data from other researches throughout in the region show the possibility of beginning karstification. Several field researches during the dry and the wet season made it possible to observe, describe and map part of the hydrological behavior of the investigated karstic systems. The obtained results pointed out that the karst that was investigated in detail has various morpholical proves and materials from preterit geomorpholical dynamics. Integrating these results with data from other researches throughout the region show the possibility of beginning karstification dating to Upper Miocene. It was also verified morphostructural control action on the development of mapped karst features. This control includes tectonic and stratigraphic structures. The last mentioned, composed of pelitic levels interleaved with carbonates, are underlying the layer composed by calcarenites, which act as karstic base level and can modify the karstic features. In the western sector of the Curral de Pedras I this occurs in a way that these levels are exposed to the surface and then eroded by processes responsible for retreat of slope which bordering the top compartments where the karstic systems are located.